Penggunaan Alat Peraga Musschenbroek Bimetal terhadap Keterampilan Proses Sains - Khozinatur Rohmah; Susilawati Susilawati; Ernawati Saptaningrum (Jurnal Penelitian Pembelajaran Fisika, 2017)
The aim of the research is to know the effect of using bimetal Musschenbroek Bimetal to the skill science processes this type of research conducted by researcher is Quasi Experimental with Non equivalent Control Group Desaign. This population of this research is all of students in Miftahul Falah Junior High school VII 2017/2018 school year which consist of thirty five until forty students. Devided seven classes are VII A, VII B, VII C, VII D, VII E, VII F, VII G, sampling technique in this research using cluster sampling technique. The experimental class was not choosen randomly but determined by the teacher and this taking sampling technique becouse the population is assismed to be normally distributed and in a homogenitas state so that selected VII A class as a contol class and VII D class as experiment class.Technique of data collection is done by using observation sheet method data collection technique were conducted using the observation sheet method skill science processes and documentation. Testing research hypotheseses show. There is significant influence  using Musschenbroek Bimetal to the students science prosess skills, in the test of the hypotheseses the researcher using taster hypothesis t right side from the result of post test show that value  tcount > ttableis  4,35 > 1,67 becouse tcount> ttable so H0  Rejected, Ha is received, so there is a difference influence on the leaning that carred on in the experimental class and control class.